Mixed Reality CAD System - Abdullah, Che Zulkhairi; Abdul Rahim, Asiah; Mohd Yusoff, Noraini; Mahadzir, Mazlan; Mohd Fadzil, Faizal Athar (2015)
This research is about the development of a „Mixed-Reality CAD system‟ with new features that provide tangible interactions and manipulation of objects and features inside a 3D environment. The system is based on Unity3D Game simulation system which is open for connections with other programming environment like Python. Python programming syntax and libraries is faster than CSharp running inside Unity3D system, and the extensive Python libraries provide for the opportunity of reading various sensors and performing complex image processing. The Mixed-Reality CAD system is divided into 4 main systems, which are input, tangible interface, visualization and projection. The input is coming from image processing that recognizes and classify features, the tangible interface is a robotic platform with n-Degree-of-Freedom with linkable snap-on modules, the visualization provide the person-view and interaction with features and the projection is a real-time projection of optimized solution for using and navigating a real built-environment.